AN INFLUENCE OF DEBT TO ASSET RATIO, TOTAL ASSET TURNOVER AND FIRM SIZE ON RETURN ON ASSET IN BUMN PERKEBUNAN NUSANTARA GROUP COMPANIES FOR THE 2016-2020 PERIOD - Aisyah Nabilla Azzahra; Anita Roosmawarni; Nurullaili Mauliddah (International Conference on Economics, Management, Business, and Accounting, 2024)
One of the state-owned companies that exists to support the national economy is the Perkebunan Group. The Company of Perkebunan Group is fully aware of the internal and external challenges related to finances as well as tight business competition, one of which is profitability which influences investors' interest in the returns provided. This research method uses multiple linear regression analysis with a purposive sampling technique. Data processing uses tools in the form of the EVIEWS 12 statistical application with the best Random Effect Model (REM) test results. The results of the f test research show that Debt to Asset Ratio, Total Asset Turnover and Firm Size simultaneously influence Return on Assets with a probability value of 0.000000. The results of the t test research show that the Debt to Asset Ratio and Total Asset Turnover variables partially influence Return on Assets, while the Firm Size variable partially has no influence on Return on Assets. The research results of the coefficient of determination in this study were 0.6553, meaning that the ability to explain the model in this study was 65.5%. So this research can be used as a consideration in evaluating the performance of the BUMN Perkebunan Nusantara Group company to increase company value